2014
DOI: 10.4055/cios.2014.6.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Physiological Efficacies of Different Intermittent Sequential Pneumatic Compression Devices in Preventing Deep Vein Thrombosis: A Prospective Randomized Study

Abstract: BackgroundThere are few comparative studies about the optimal method of pneumatic compression to prevent deep vein thrombosis (DVT). The aim of this prospective randomized study was to compare venous hemodynamic changes and their clinical influences between two graded sequential compression groups (an alternate sequential compression device [ASCD] vs. a simultaneous sequential compression device [SSCD]).MethodsIn total, 34 patients (68 limbs) undergoing knee and spine operations were prospectively randomized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Pneumatic CS alone reduce the incidence of DVT/PE in patients undergoing spinal surgery. [ 4 10 ] To reduce the risk of DVT/PE in lumbar surgery, Epstein promoted CS prophylaxis alone in 139 patients undergoing multilevel lumbar laminectomies (average 3.8 levels) and instrumented fusions (average 1.4 levels) [ Table 2 ]. [ 4 ] Low dose heparin (LDH) prophylaxis was not used to avoid the risk of postoperative hematoma/seroma and/or wound breakdown/dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumatic CS alone reduce the incidence of DVT/PE in patients undergoing spinal surgery. [ 4 10 ] To reduce the risk of DVT/PE in lumbar surgery, Epstein promoted CS prophylaxis alone in 139 patients undergoing multilevel lumbar laminectomies (average 3.8 levels) and instrumented fusions (average 1.4 levels) [ Table 2 ]. [ 4 ] Low dose heparin (LDH) prophylaxis was not used to avoid the risk of postoperative hematoma/seroma and/or wound breakdown/dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…compared the relative efficacy of two types of sequential compression devices (SCD's) to avoid DVT in 34 patients (68 limbs) undergoing knee and spine operations [Tables 1 and 2 ]. [ 10 ] Patients recieved either ASCD vs. SCCD (variants of compression stockings). All were followed with routine lower extremity Doppler's performed on the 4 th and 7 th postoperative days.…”
Section: Discussionmentioning
confidence: 99%
“…About half of all untreated DVT cases are complicated by PE, and, on the contrary, 50% to 80% of all untreated PE cases are related to DVT. [2,3] Attention must be paid on VTE for surgeons, and increasing studies reported on risk factors of VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature and international guidelines on VTE emphasize that prevention is more important and cost-effective than treatment, because once VTE develops, it can only be cured at considerable expense. Although approximately two-thirds of all VTE events result from hospitalization, only one-third of all hospitalized patients at risk receive adequate prophylactic treatment 10 . Currently, common prophylactic treatment mainly includes two types of therapies.…”
mentioning
confidence: 99%